The demand for child care quality: an hedonic price theory approach. - Hagy, Alison P. (Journal of Human Resources)
I use an hedonic price theory approach to estimate the demand for child care quality. Two complementary surveys, the National Child Care Survey, 1990 (NCCS) and the Profile of Child Care Settings Study (PCS), allow me to derive an implicit price for staff-to-child ratio. I use this price as an explanatory variable in a demand equation for this quality attribute. Direct purchase-of-service contracts or voucher programs, by subsidizing only those providers that satisfy state regulatory requirements, effectively lower the implicit price of regulated attributes, such as staff-to-child ratio. Results of this study suggest that such tied subsidies have almost no influence on the demand for child care quality. Reprinted by permission of the publisher.